The connectivity of lymphogenous and hematogenous tumor cell dissemination: biological insights and clinical implications - Sleeman, Jonathan P.; Cady, Blake; Pantel, Klaus (Clinical & experimental metastasis, 2012)
Although tumor cells are found in the blood early after tumorigenesis, dissemination through the lymphatic system and in particular the formation of lymph node metastases has long been considered to be a driving force behind the formation of secondary tumors in distant vital organs. Contemporary experimental observations and clinical trial results suggest that this may not be the case. In this review we survey the evidence for both points of view, and examine the hypothesis that the prognostic relevance of lymph node metastases may lie in their ability to indicate that primary tumors are producing soluble factors that have the potential to promote metastasis at these distant sites, for example by releasing tumor cells from dormancy. Furthermore, the interconnectivity between the lymphatic and blood circulatory systems underscores the relevance of the analysis of the properties of circulating and disseminated tumor cells for prognostic evaluation, patient stratification and understanding the biology of metastasis. We therefore give an overview of the current state of the art in this field.
Published 06 June 2012
Gesehen am 18.10.2018